Subunit IV of yeast cytochrome c oxidase: cloning and nucleotide sequencing of the gene and partial amino acid sequencing of the mature protein. - Maarse, A C (1984)
The six small subunits (IV-VII, VIIa, VIII) of yeast cytochrome c oxidase are encoded by nuclear genes and imported into the mitochondria. We have isolated the gene for subunit IV from a yeast genomic clone bank and determined its complete nucleotide sequence. We have also isolated subunit IV from purified yeast cytochrome c oxidase and determined most of its amino acid sequence which confirms the positioning of approximately 90% of the amino acid residues. The sequence comparison shows that the coding sequence of the gene lacks introns and that subunit IV is made as a precursor with an amino-terminal extension of 25 residues, five of which are basic and none of them acidic. Precursor processing involves cleavage of a Leu-Gln bond.